An Open Innovation Framework for Market Driven Sustainable Food Manufacturing - Makatsoris, Charalampos; Tsimiklis, Panagiotis (Food studies, 2015)
Traditional closed innovation has been used for many years within the food industry. However, this sector recently has been perceiving its end-user to be wary of radically new products and changes in consumption patterns. We propose a new framework that embraces the Open Innovation approach for harvesting attitudes and perceptions from consumers and gathering information from the web. The proposed framework is cross cutting, as it extends beyond New Product Development by integrating processes designed to use that information to directly drive the development of new product recipes and subsequently drive product specification and, ultimately, production. This is achieved by evolving and translating the information resulting from each stage in our framework into actionable formats for the next. The framework results into Bill-of-Materials, Machinery and Installation requirements, Process Plans, and ultimately deploys the new products into manufacturing. Within that last part of the framework, we can achieve cost reduction targets, subject to availability of raw materials and ingredients, required delivery times, and production capacity constraints. The proposed approach of this work is envisaged to improve innovation delivery in the food industry by drastically reducing the lead time which new products are conceived, validated, specified, and produced and, importantly, include the consumer and selected suppliers in the loop by allowing preferences not only to influence but to drive the New Product Development and manufacturing processes.